Comparative Analysis of Article 21 Income Tax Calculation to Make Income Tax Expenses Efficient (Case Study at PT. BTS) - N S Yulianti; I D M Partika; I M S A Jaya (Journal of Applied Sciences in Accounting, Finance, and Tax, 2019)
For a company tax is a burden that can reduce the amount of profit earned, so the company needs to perform an action to minimize the amount of tax payable. Effort to minimize tax in accordance with tax provisions are often referred to tax planning. Tax planning for income tax article 21 is very important for a company, because in addition to earn a profit as much as possible, the company must also pay attention to the welfare of its employees. In conducting a tax planning, in addition to pay attention to the welfare of its employees, the company must also consider the impact of tax planning for the company, so that a company should choose the right method in the calculation of taxes, especially income tax article 21. This research intended to determine the effect of tax planning comparative in three policies/ cutting methods of Tax Article 21 in an effort to efficiently tax payable on PT. BTS. Type of data used in this research is secondary data obtained through the documentation and data analysis technique used is quantitative descriptive. Based on the research results, comparison of the calculation of income tax article 21 by using gross method, net method, and gross up method, the most efficient is gross up method or giving allowances amounted to taxes payable. From the comparison of the three calculations performed, gross up method generating efficiency of the corporate income tax payable in 2017 amounting to Rp 286.786.757,00 compared to other methods. But because of replace enjoyment into allowances, the company paid an additional income tax article 21 amounting to Rp 118.117.750,00, so the total corporate income tax savings after an increase in income tax article 21 is Rp 168.669.007,00. (Rp 286.786.757,00 - Rp 118.117.750,00).